Chronicle of John of Nikiu and Ethiopic chronographs - Ekaterina Gusarova (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
In the frame of the present research an attempt was made to discover continuity between the text of the Chronicle of John of Nikiu, translated from Arabic into Geez in the very beginning of the 17th century, the Ethiopian Chronographs, translated from Arabic in the 16th century and the universal history accounts, that form the initial part of the collections of the chronicles of Ethiopian kings. As the main example of chronograph the text attributed to al-Makîn from the manuscript Eth. 29 from the fonds of the Institute of Oriental manuscripts (St Petersburg) was taken. In particular, due to the large volume of the texts, the chapter dedicated to the Roman Emperors was chosen for the comparative analysis. The study of the corresponding parts of the compilations revealed a series of common features, especially in the way of dating events and attributing certain events to the Emperor’s reigns. Moreover, we managed to identify a number of concurrences in the way of describing some events. Wherein in the Chronopraph there are subjects, that do not take part of the Chronicle of Juhn of Nikiu, that means that different sources were usen when compiling the two operas. The comparison was also realized through additional historical writings. The analysis of the texts demonstrates that the compilations in question are interconnected by the form and content. This reflects the specific features of the translated annals that don’t represent an integral part of classical Ethiopic historiography. Besides we managed to show that the translated operas left their marks in the local chronicles, compiled at that time in Ethiopia.